Integrasi Prinsip ESG dan Keuangan Etis Islam dalam Pembentukan Portofolio Investasi Syariah: Sebuah Kerangka Konseptual - Muhammad Farras Hanif; Ai Kokoy Koyyimah (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: This study aims to examine the integration of Environmental, Social, and Governance (ESG) principles and Islamic ethical finance in developing Islamic investment portfolios. Currently, Islamic investments emphasize Shariah compliance rather than prioritizing social and environmental aspects in stock screening. This study proposes a more comprehensive Islamic investment portfolio framework by aligning Islamic principles with sustainable finance practices to bridge this gap. Research Methods: This study uses a qualitative descriptive approach with literature studies from various sources such as journals, regulations, and related documents. Results: The results of this study indicate that ESG aligns with the Maqasid Al-Shariah principles and can be used as a complement to the investment selection process. The study proposes a conceptual framework for integrating ESG and Islamic ethical finance through several key stages, including Sharia screening, ESG screening, ethics-based portfolio development, and continuous governance and monitoring. Conclusion: This study contributes by offering a conceptual model for integrating ESG and Islamic ethical finance into Islamic investment portfolio management. The proposed framework provides practical implications for investors and the Islamic finance industry in developing more sustainable, ethical, and socially responsible investment strategies, while also opening avenues for future empirical research.